(untitled) (Studia theodisca, 2011)
Ludwig Tieck is not only the most productive and stimulating power of German Romanticism with respect to literature but also, largely unnoticed by his contemporaries and critics, an innovative proponent of a new art. His Sternbald goes way beyond the position of Wackenroder’s Herzensergießungen from which it started. It not only influenced the artwork of the two most important romantic painters, Philipp Otto Runge and Caspar David Friedrich, but advocates, in a way, twentieth-century ideas of modern painting.